Preparation method of self-healing and reconfigurable integrated Janus nanofiber photo-thermal film

By preparing Janus nanofiber photothermal films and utilizing DA dynamic bonds to achieve interfacial covalent bonding and self-healing, the problem of poor stability of Janus photothermal films in seawater desalination was solved, and long-term stable seawater desalination performance and self-healing ability were achieved.

CN121047040APending Publication Date: 2025-12-02HANGZHOU VOCATIONAL & TECHN COLLEGE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510391472.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Existing Janus photothermal membranes are susceptible to salt ion blockage and have weak interfacial bonding properties during seawater desalination, resulting in poor long-term stability and insufficient resistance to chemical and mechanical damage.

Method used

Janus nanofiber photothermal films were prepared by electrospinning using dynamic polymers of polyethylene glycol-based polyurethane (PPG@PU) and polydimethylsiloxane polyurethane (PDMS@PU). The interfacial covalent bonds were achieved by utilizing DA dynamic bonds, and self-healing and reconstruction were achieved by using an infrared point light source.

Benefits of technology

The interfacial bonding of Janus nanofiber photothermal film was improved, achieving long-term stable seawater desalination performance, self-healing ability and remodeling ability, while maintaining the stability of water evaporation rate and photothermal performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121047040A_ABST
    Figure CN121047040A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of seawater desalination materials, and particularly relates to a self-healing and reconfigurable integrated Janus nanofiber membrane as well as a preparation method and application thereof. According to the preparation method of the Janus nanofiber photo-thermal film, two dynamic polymers including hydrophilic polyethylene glycol polyurethane (PPG) and hydrophobic polydimethylsiloxane polyurethane (PDMS) and PU are synthesized on the basis of a dynamic Diels-Alder bond, and then the PPG and PU and PDMS and PU-CNTs Janus double-layer nanofiber photo-thermal film is prepared through continuous electrostatic spinning. The upper layer and the lower layer of the prepared Janus photo-thermal film have different wettability, interfaces are combined through covalent bonds, and the interface bonding force is 22 N * m < 1 >. The stable evaporation rate of 1.34 kg.m < 2 >. H < 1 > is realized under the illumination of 1 kW. M < 2 >; reversible dissociation of the dynamic bond cross-linked network enables the Janus nanofiber membrane to have self-healing and reconfigurable capabilities and keep the photo-thermal performance of the Janus nanofiber membrane. The dynamic cross-linked polymer is applied to preparation of the Janus electrostatic spinning nanofiber photo-thermal film, and the problems of weak interface bonding force and poor durability and sustainability of the Janus electrostatic spinning nanofiber photo-thermal film are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solar-driven interface water evaporation technology, specifically relating to a method for preparing a self-healing, reconfigurable integrated Janus nanofiber photothermal film. Background Technology

[0002] Janus membranes are asymmetric membrane materials with bifacial functions. Due to the different physical or chemical properties of their two sides, they have wide applications in separation and purification, energy and environment, and biomedicine.

[0003] Freshwater scarcity has become a global challenge, exacerbated by climate change, population growth, and accelerated industrialization. Seawater desalination, which converts solar energy into thermal energy through localized heating and interfacial evaporation, is an effective way to obtain clean water. Photothermal conversion fiber membranes, with their high porosity and permeability, are considered ideal materials for photothermal conversion. However, in the seawater desalination process, salt ions easily clog the fibers of single-layer photothermal conversion fiber membranes, leading to membrane fouling. Janus photothermal membranes effectively block salt ions in a hydrophobic layer, preventing salt contamination. However, Janus photothermal membranes have weak interfacial bonding properties, making them prone to peeling in long-term saline environments. Furthermore, their poor resistance to chemical and mechanical damage hinders their long-term stable use. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing a self-healing, reconfigurable, integrated Janus nanofiber photothermal film. The Janus nanofiber photothermal film prepared by this invention can achieve strong interfacial bonding and realize long-term stable photothermal conversion and evaporation performance in seawater.

[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0006] This invention provides a method for preparing a self-healing, reconfigurable integrated Janus nanofiber photothermal film, comprising the following steps:

[0007] (1) Preparation of a dynamic polymer of polyethylene glycol-based polyurethane (PPG@PU);

[0008] (2) Preparation of dynamic polymer of polydimethylsiloxane polyurethane (PDMS@PU);

[0009] (3) Electrospinning the PPG@PU mixed solution to obtain a hydrophilic nanofiber membrane;

[0010] (4) A hydrophilic / hydrophobic Janus nanofiber photothermal film was obtained by electrospinning a mixed solution of PDMS@PU and carbon nanotubes (CNTs) onto a PPG@PU nanofiber membrane.

[0011] Preferably, the preparation of the PPG@PU and PDMS@PU dynamic polymers is based on the Diels-Alder (DA) dynamic reaction of furan and bismaleimide, and the reaction formula is as follows:

[0012] Preferably, the DA reaction is a reversible reaction, specifically characterized by rapid dissociation at high temperature (120°C) and slow binding at low temperature, which provides a processing time window for electrospinning.

[0013] The structural formulas of the PPG@PU and PDMS@PU dynamic polymers are as follows:

[0014] (I)

[0015] (II)

[0016] Preferably, the synthesis method in step (1) includes: adding PPG (12 g, 12 mmol) to a glass reactor equipped with a magnetic stirrer and drying it under vacuum at 110°C for 2 hours. After cooling to 80°C, adding MDI (7.5 g, 30 mmol) dropwise to the reactor under a nitrogen atmosphere for 2 hours. After cooling to 60°C, adding 2,2-bis(hydroxymethyl)propionic acid (0.8049 g, 6 mmol), 2,5-furandiethanol (1.5375 g, 12 mmol), and THF (30 mL), and reacting for 24 h. Finally, removing the solution under vacuum at 50°C.

[0017] Preferably, in step (1), the molar ratio of PPG:MDI:2,2-bis(hydroxymethyl)propionic acid:2,5-furandiethanol is 2:3:1:2.

[0018] Preferably, the synthesis method in step (2) includes adding HDPDMS (12 g, 12 mmol), IPDI (5.3352 g, 24 mmol), 2,5-furandiethanol (1.5375 g, 12 mmol), and THF (15 mL) to a glass reactor equipped with a magnetic stirrer. The system is then heated to 60°C and reacted for 17 h. Finally, the solution is removed under vacuum at 50°C.

[0019] Preferably, in step (2), the molar ratio of HDPDMS:IPDI:2,5-furandimethyl is 1:2:1.

[0020] Preferably, the PPG@PU solution in step (3) includes PPG@PU, crosslinking agent bismaleimide, and N,N-dimethylformamide.

[0021] Preferably, the mass fraction of PPG@PU polymer in the PPG@PU solution in step (3) is 50 wt.%.

[0022] Preferably, the electrospinning parameters for the PPG@PU mixed solution in step (3) are: spinning voltage: 12 KV, spinning distance: 15 cm, and spinning speed: 0.5 mL·h. -1 The temperature is controlled at 25±3℃ and the humidity is approximately 40%±5%.

[0023] Preferably, the PDMS@PU solution in step (4) includes PDMS@PU, crosslinking agent bismaleimide, N,N-dimethylformamide, and photothermal material carbon nanotubes.

[0024] Preferably, in step (4), the mass fraction of PPG@PU polymer in the PPG@PU solution is 45 wt.%.

[0025] 13. The preparation method according to claim 9 or 11, characterized in that the content of the crosslinking agent bismaleimide in the PDMS@PU solution is 1.6 wt.%.

[0026] Preferably, the content of photothermal material carbon nanotubes in the PDMS@PU solution in step (4) is 0.1-0.5%.

[0027] Preferably, the electrospinning parameters for the PDMS@PU mixed solution in step (4) are: spinning voltage: 5-15 KV, spinning distance: 5-15 cm, and spinning speed: 0.3-3 mL·h. -1 The temperature is controlled at 25±3 ℃ and the humidity is about 40%±5%.

[0028] Preferably, the hydrophilic / hydrophobic Janus nanofiber photothermal film in steps (3) and (4) needs to be left to stand for 72 hours.

[0029] This invention also provides a Janus nanofiber photothermal film obtained by the preparation method described above. The Janus nanofiber photothermal film includes a hydrophobic nanofiber photothermal conversion layer and a hydrophilic nanofiber membrane. The PPG@PU layer and PDMS@PU layer in the Janus nanofiber photothermal film have the same DA dynamic bond structure, which can be intercalated at the interface to achieve covalent bonding at the interface. Both the PPG@PU layer and PDMS@PU layer in the Janus nanofiber photothermal film have DA dynamic bond structures, which can achieve re-healing of cracks by irradiating the fracture site with an infrared point light source when the nanofiber membrane is broken. Both the PPG@PU layer and PDMS@PU layer in the Janus nanofiber photothermal film have DA dynamic bond structures. After heating at 120°C for 10 min, the cross-linked structure of the polymer re-dissociates into a linear structure, which can be reprocessed by electrospinning to achieve reconstruction of the Janus nanofiber photothermal film.

[0030] This invention also provides the application of Janus nanofiber photothermal membrane in the field of seawater desalination.

[0031] Beneficial effects This invention designs two crosslinked polymers, PPG@PU and PDMS@PU, with different wetting properties containing DA dynamic bonds, to prepare a self-healing and reconfigurable monolithic Janus nanofiber photothermal membrane. The photothermal layer of the Janus nanofiber photothermal membrane exhibits hydrophobic properties. The two dynamic polymers, PPG@PU and PDMS@PU, possess the same dynamic bonds, enabling them to intercalate at the interface and effectively improving the bonding force at the hydrophilic-hydrophobic interface. Simultaneously, the "fast dissociation-slow binding" characteristic of DA dynamic bonds provides a time window for electrospinning and endows the Janus nanofiber photothermal membrane with self-healing and reconfigurable capabilities, achieving long-term stable seawater desalination performance.

[0032] Data from the examples show that at 1 kW·m -2 Under high solar radiation intensity, the water evaporation rate of the Janus nanofiber photothermal film prepared in this invention is 1.34 kg·m⁻². -2 ·h -1 Covalent bonding was achieved at the interface, increasing the bonding strength at the interface to 22 N·m. -1 It has a self-cleaning function, which can effectively slow down the salting-out effect and keep the water evaporation rate stable for 6 consecutive hours; the water evaporation rate of the Janus nanofiber photothermal film remains basically unchanged after self-healing and reconstruction. Attached Figure Description

[0033] Figure 1 For the selection and design of DA dynamic keys.

[0034] Figure 2 This describes the synthesis process of PPG@PU dynamically crosslinked polymers.

[0035] Figure 3 This describes the synthesis process of PDMS@PU dynamically crosslinked polymer.

[0036] Figure 4 (a) is the NMR spectrum of the linear PPG@PU prepolymer; Figure 4 (b) is the NMR spectrum of the PDMS@PU linear prepolymer.

[0037] Figure 5 FTIR spectra of PPG@PU linear prepolymer; Figure 5 (b) is the FTIR spectrum of the PDMS@PU linear prepolymer.

[0038] Figure 6 The wetting properties of the upper PDMS@PU-CNTs and lower PPG@PU layers of the Janus nanofiber photothermal film.

[0039] Figure 7 SEM images of Janus nanofiber photothermal film: (a1, a2) lower layer PPG@PU; (b1, b2) upper layer PDMS@PU-CNTs.

[0040] Figure 8 (a) is the molecular formula at the cross-linking point of the two polymer layers; Figure 8 (b) is a SEM image of the cross-section of the Janus nanofiber photothermal film.

[0041] Figure 9 The displacement-stretch curve of the Janus nanofiber photothermal film after 90° peeling is shown.

[0042] Figure 10 This is a photograph of the Janus nanofiber photothermal film after a three-stage cutting-and-healing experiment.

[0043] Figure 11 (a) Tensile fracture curve of Janus nanofiber photothermal film after three cut-and-heal cycles; (b) Healing efficiency.

[0044] Figure 12 Photothermal evaporation performance of Janus nanofiber photothermal film in 3.5 wt.% saline solution was tested.

[0045] Figure 13Remodeling experiments of Janus nanofiber photothermal film: (a) PDMS@PU-CNTs film after being cut; (b) PDMS@PU-CNTs film after being heated at 120°C dissolved in DMF solution; (c) PDMS@PU-CNTs film without heating treatment insoluble in DMF solution; (d) PDMS@PU film after being cut; (e) PDMS@PU film after being heated at 120°C dissolved in DMF solution; (f) PDMS@PU film without heating treatment insoluble in DMF solution.

[0046] Figure 14 The photothermal evaporation performance of the reshaped Janus nanofiber photothermal film was tested. Detailed Implementation

[0047] The present invention will be further described below with reference to specific embodiments.

[0048] Reagent sources: Polypropylene glycol (PPG), 4,4'-diphenylmethane diisocyanate (MDI), 2,2-bis(hydroxymethyl)propionic acid, 2,5-furandimethylethanol (98%+), tetrahydrofuran (THF), and hydroxyl-terminated polydimethylsiloxane (HDPDMS, molecular weight 1000) were purchased from Maclean's Biochemical Technology Co., Ltd. Isophorone diisocyanate (IPDI, 99%) and N,N-dimethylformamide (DMF, analytical grade) were provided by Sinopharm Chemical Reagent Co., Ltd. Bismaleimide (BMI, 95%), sodium chloride, zinc sulfate heptahydrate, and calcium chloride were purchased from Aladdin Reagent Co., Ltd. Multi-walled carbon nanotubes (length 10-30 µm, diameter 5-15 nm) were purchased from Sinopharm Nano (Jiangsu) Co., Ltd.

[0049] Characterization and testing.

[0050] FTIR spectra were recorded using a Perkin Elmer, Spectrum BXⅡ instrument. Characterization and measurements were performed using a Bruker Avance 600 NMR spectrometer (Avance 3 HD 600 MHz, China). Chemical shifts (δ) relative to the residual solvent signal (DMF) are reported in ppm. Measurements were taken using an electronic universal testing machine (Changchun Kexin Testing Instruments Co., Ltd., WDW3020) at a speed of 100 mm·min⁻¹. −1Mechanical properties of the samples were tested at the tensile rate. A self-healing experiment was conducted using a near-infrared (NIR) point light source (808 nm) with an output power of 582 mW. Several Janus electrospun films (length × width = 20 mm × 10 mm) were prepared to test their self-healing properties. The samples were cut in half with a blade, and then the broken edges were quickly aligned and joined under an 808 nm infrared lamp for 2 minutes to achieve healing of the Janus nanofiber photothermal film. Healing was performed at 10°C·min under a N2 atmosphere using a thermogravimetric analyzer (TA, USA). −1 The heating rate was controlled for TGA testing of PPG@PU and PDMS@PU, with a temperature range of 40-500°C. The surface morphology of the Janus nanofiber photothermal film was characterized using field emission scanning electron microscopy (FE-SEM) (China, SU8010). The water contact angle of the PPG@PU and PDMS@PU nanofiber films was measured using an optical contact angle apparatus (OCA15EC, Data Physics, Germany). The interfacial bonding strength of various Janus nanofiber photothermal films was measured using a standard 90° peel test (INSTRON / 5969 electronic universal testing machine). PPG@PU and PDMS@PU-CNTs films were cut into small pieces and placed in sample vials, with a certain amount of N,N-dimethylformamide (DMF) added. Both films were treated in an oven at 120°C for 15 minutes; then the system was cooled to room temperature to prepare a spinning solution of the original concentration and spun. This process was repeated three times for recovery testing.

[0051] Example 1.

[0052] Synthetic route of linear polymer PPG@PU:

[0053]

[0054] Polypropylene glycol (PPG, 12 g, 12 mmol) was added to a glass reactor equipped with a magnetic stirrer and dried under vacuum at 110 °C for 2 h. After cooling to 80 °C, diphenylmethane diisocyanate (MDI, 7.5 g, 30 mmol) was added dropwise to the reactor under a nitrogen atmosphere over a period of 2 h. After cooling to 60 °C, 2,2-bis(hydroxymethyl)propionic acid (0.8049 g, 6 mmol), 2,5-furandiethanol (1.5375 g, 12 mmol), and tetrahydrofuran (THF, 30 mL) were added, and the reaction was allowed to proceed for 24 h. Finally, the solution was removed under vacuum at 50 °C.

[0055] Synthetic route of linear polymer PDMS@PU:

[0056]

[0057] Hydroxyl-terminated polydimethylsiloxane (HDPDMS, 12 g, 12 mmol), isophorone diisocyanate (IPDI, 5.3352 g, 24 mmol), 2,5-furandiethanol (1.5375 g, 12 mmol), and tetrahydrofuran (THF, 15 ml) were added to a glass reactor equipped with a magnetic stirrer. The system was then heated to 60 °C and reacted for 17 h. Finally, the solution was removed under vacuum at 50 °C.

[0058] The molecular structure of the prepolymers was confirmed by nuclear magnetic resonance (NMR). The NMR results and signal assignments for the PPG@PU and PDMS@PU prepolymers are shown below. Figure 4 As shown in a and b, the signals of the hydrogen atoms are basically consistent with the positions predicted in the ChemDraw software, indicating that the chemical structure of the polymer is basically consistent with the expected results.

[0059] The structure was further characterized by infrared spectroscopy. The infrared absorption spectra of the PPG@PU and PDMS@PU prepolymers are shown below. Figure 5 As shown in a and b, 2275cm -1 The asymmetric stretching vibration absorption peak at 3300 cm⁻¹ was almost unobservable, indicating that the isocyanate group reacted completely. Meanwhile, the absorption peak at 3300 cm⁻¹... -1 and 1719cm -1 The nearby absorption peaks are attributed to the stretching vibrations of NH and C=O, respectively, indicating that the isocyanate reacts with the hydroxyl group to form a urethane structure. In conclusion, the PPG@PU and PDMS@PU prepolymers were successfully synthesized as designed.

[0060] A mixture of bismaleimide (BMI, 1.6 wt.%) and N,N-dimethylformamide (DMF) was continuously stirred for 5 h and 3 h at room temperature to prepare PPG@PU solutions with mass fractions of 50 wt.% and PDMS@PU solutions, respectively. Carbon nanotubes (CNTs) were dispersed in the PDMS@PU / DMF solutions by ultrasonic treatment to prepare spinning solutions. The obtained PPG@PU spinning solutions were electrospun for 4 h at a spinning voltage of 12 kV, a spinning distance of 15 cm, and a spinning rate of 0.5 ml·h⁻¹. The PDMS@PU-CNTs / DMF spinning solution was then continuously electrospun on the prepared PPG@PU film for 2 h at a spinning voltage of 10 kV, a spinning distance of 15 cm, and a feed rate of 1.8 ml·h⁻¹. During the electrospinning process, the indoor temperature was controlled at 25±3℃ and the humidity at 40%±5%.

[0061] The prepared Janus nanofiber photothermal film was left to stand for 36 h.

[0062] Water contact angle tests were used to evaluate the wettability of materials. For example... Figure 8 As shown, the water contact angle on the PPG@PU side of the Janus nanofiber photothermal film is 46.0°, exhibiting hydrophilicity; the water contact angle on the PDMS@PU-CNTs side is 138.9°, exhibiting hydrophobicity. The Janus nanofiber photothermal film is a typical hydrophilic / hydrophobic heterostructure.

[0063] Figure 9 The images show scanning electron microscope (SEM) images of the bottom and top layers of the Janus nanofiber membrane prepared in Example 1. As can be seen, both the bottom and top layers of the Janus nanofiber photothermal membrane exhibit an open three-dimensional network structure, and the fibers are self-supporting.

[0064] The hydrophilic and hydrophobic interfaces of the Janus nanofiber photothermal film are linked by covalent bonds, and the chemical formulas of the two polymer networks intercalated are as follows: Figure 8 As shown in Figure a, the SEM image of the cross-section ( Figure 8 b) It can be seen that the Janus nanofiber photothermal film has a tight connection at the hydrophilic / hydrophobic interface and no obvious layered structure.

[0065] A portion of the Janus nanofiber photothermal film was manually peeled off, providing an initial peeling arm that could be clamped by a load device. The sample was then mounted, and the peeling angle was maintained at 90° throughout the tensile process. The 90° peeling experiment demonstrated that the bonding force between the hydrophilic and hydrophobic layers of the Janus nanofiber photothermal film was 22 N·m. −1 This improves the overall structural stability of the fiber membrane. Figure 11 ).

[0066] The Janus nanofiber photothermal film was cut in half with a knife, and then the two halves were tightly rejoined. The broken section of the fiber film was then irradiated with 808 nm infrared light for 2 minutes. The Janus film reconnected at the break, restoring its structural integrity. This cut-and-heal process was repeated three times. The healed film looked like... Figure 12 As shown.

[0067] Tensile tests were used to further characterize the healing ability of the Janus nanofiber photothermal film. The fracture stress of the healed Janus nanofiber photothermal film recovered to 1.6 MPa. Figure 13 a) The stress, strain, and toughness recovered to 98.3%, 91.4%, and 87.8% of the original sample, respectively, indicating that it has good self-healing ability. Figure 13 b).

[0068] At 1 kW·m -2Under sunlight, the hydrophobic upper layer of PDMS@PU-CNTs undergoes photothermal conversion, while the hydrophilic layer of PPG@PU facilitates continuous water transport. Vapor is generated at the hydrophilic / hydrophobic interface, and salt ions are directly blocked at the interface and redissolve into the water below. The evaporation rate of the Janus nanofiber photothermal film is 1.34 kg·m³. -2 ·h -1 Monitoring of Janus nanofiber photothermal film at 1 kW·m -2 Evaporation performance under continuous sunlight for 12 hours ( Figure 14 The evaporation rate remains almost constant throughout the process, demonstrating good photothermal performance.

[0069] Janus nanofiber photothermal film has remodeling properties.

[0070] The Janus nanofiber photothermal film was peeled into two layers and cut into small pieces. Figure 13 a) and d) were placed in a DMF solution, and the fiber membrane did not dissolve, exhibiting characteristics of a thermosetting polymer. Figure 13 c, f). The above solution was heated at 120°C (DA reaction temperature) for 15 min. The DA addition structure re-dissociated into furan and maleimide units via the Retro Diels-Alder (rDA) reaction at high temperature. The covalent cross-linked network in the material temporarily disappeared, restoring the linear structure and exhibiting thermoplastic properties. After stirring at room temperature for 10 min, it could be dissolved in DMF and other organic solvents. Figure 13 b, e) can be reused in electrospinning to reshape Janus nanofiber photothermal films. This reshaping experiment was conducted three times, and after cycling, the photothermal performance of the Janus nanofiber photothermal film was almost identical to that of the original evaporator. Figure 14 ).

[0071] This synthetic material may offer more advantages than previously reported materials in the field of solar-interface seawater desalination. In practical applications, strong light, highly oxidizing chemicals, and chemical oxidation by organic solvents often lead to evaporator failure. Therefore, materials with cross-linked structures not only remain stable at room temperature but can also be dissolved and reprocessed after heat treatment; their recombination capability is an effective way to extend the material's lifespan.

[0072] This invention utilizes two dynamic materials, PPG@PU and PDMS@PU, prepared based on reversible DA bonds, and electrospins them to obtain a hydrophilic-hydrophobic bilayer Janus nanofiber photothermal membrane for solar-driven interfacial seawater desalination. The covalent bonding between the two nanofiber layers significantly improves structural stability during operation. Furthermore, the Janus membrane exhibits self-healing properties through the DA reaction, maintaining its mechanical and photothermal properties before and after healing. In a 3.5 wt.% NaCl solution, it achieves a stable evaporation rate of 1.34 kg·m³ within 5 h. −2 ·h −1 No salt accumulation occurs. Furthermore, the entire device is reconfigurable, with almost identical evaporation rates before and after reconfiguration. These new materials and design principles will inspire a range of next-generation solar-powered steam desalination evaporation devices.

Claims

1. A method for preparing a self-healing, reconfigurable integrated Janus nanofiber photothermal film, characterized in that, Includes the following steps: Preparation of dynamic polymers of polypropylene glycol-based polyurethane (PPG@PU); Preparation of dynamic polymers of polydimethylsiloxane polyurethane (PDMS@PU); Hydrophilic nanofiber membranes were obtained by electrospinning a PPG@PU mixed solution. A hydrophilic / hydrophobic Janus nanofiber photothermal film was obtained by continuously electrospinning a mixed solution of PDMS@PU and carbon nanotubes (CNTs) onto a PPG@PU nanofiber membrane.

2. The preparation method according to claim 1, characterized in that, The preparation of the PPG@PU and PDMS@PU dynamic polymers is based on the DA dynamic reaction of furan and bismaleimide, and the reaction formula is as follows:

3. The dynamic key according to claim 2, characterized in that, The DA reaction is a reversible reaction, characterized by rapid dissociation at high temperature (120℃) and slow binding at low temperature, which provides a processing time window for electrospinning.

4. The preparation method according to claim 1, characterized in that, The structural formulas of the PPG@PU and PDMS@PU dynamic polymers are as follows: (1) (2) 5. The preparation method according to claim 2, characterized in that, The synthesis method of (1) includes: PPG (5-15 mmol) was added to a glass reactor equipped with a magnetic stirrer and dried under vacuum at 110 °C for 2 hours. After cooling to 80 °C, MDI (10-30 mmol) was added dropwise to the reactor under a nitrogen atmosphere for 1-10 hours. After cooling to 60 °C, 2,2-bis(hydroxymethyl)propionic acid (1-10 mmol), 2,5-furandiethanol (1-24 mmol), and THF (10-60 mL) were added, and the reaction was allowed to proceed for 5-48 hours. Finally, the solution was removed under vacuum at 50 °C.

6. The preparation method according to claim 5, characterized in that, The molar ratio of PPG:MDI:2,2-bis(hydroxymethyl)propionic acid:2,5-furandiethanol is 2-5:3:1-5:2-5.

7. The preparation method according to claim 2, characterized in that, The synthesis method of (2) includes: HDPDMS (1-20 mmol), IPDI (2-30 mmol), 2,5-furandiethanol (1-12 mmol), and THF (5-80 mL) were added to a glass reactor equipped with a magnetic stirrer. The system was then heated to 50-70 °C and reacted for 5-20 h. Finally, the solution was removed under vacuum at 50-80 °C.

8. The preparation method according to claim 7, characterized in that, The molar ratio of HDPDMS:IPDI:2,5-furandimethyl is 1-6:2:1-6.

9. The preparation method according to claim 1, characterized in that, The PPG@PU solution includes PPG@PU, crosslinking agent bismaleimide, and N,N-dimethylformamide.

10. The preparation method according to claim 1, characterized in that, The PPG@PU polymer in the PPG@PU solution has a mass fraction of 50 wt.%.

11. The preparation method according to claim 1, characterized in that, The PDMS@PU solution includes PDMS@PU, crosslinking agent bismaleimide, N,N-dimethylformamide, and photothermal material carbon nanotubes.

12. The preparation method according to claim 1, characterized in that, The PPG@PU polymer in the PPG@PU solution has a mass fraction of 45-80 wt.%.

13. The preparation method according to claim 9 or 11, characterized in that, The crosslinking agent bismaleimide in the PDMS@PU solution contains 1-10 wt.%.

14. The preparation method according to claim 11, characterized in that, The content of carbon nanotubes, a photothermal material, in the PDMS@PU solution is 0.1-0.5%.

15. The preparation method according to claim 1, characterized in that, The electrospinning parameters for the PPG@PU mixed solution are as follows: Spinning voltage: 5-15KV, spinning distance: 5-50cm, spinning speed: 0.5-5mL·h -1 The temperature is controlled at 25±3℃, and the humidity is approximately 40%±5%.

16. The preparation method according to claim 1, characterized in that, The electrospinning parameters for the PDMS@PU mixed solution are as follows: Spinning voltage: 5-15KV, spinning distance: 5-50cm, spinning speed: 0.5-5mL·h -1 The temperature is controlled at 25±3℃, and the humidity is approximately 40%±5%.

17. The preparation method according to claim 1, characterized in that, The hydrophilic / hydrophobic Janus nanofiber membrane needs to be left to stand for 24-72 hours.

18. The Janus nanofiber photothermal film obtained by the preparation method according to any one of claims 1 to 17, characterized in that, The Janus nanofiber photothermal film comprises a hydrophobic nanofiber photothermal conversion layer and a hydrophilic nanofiber membrane.

19. The Janus nanofiber photothermal film obtained by the preparation method according to claim 1, characterized in that, The PPG@PU layer and PDMS@PU layer in the Janus nanofiber photothermal film have the same DA dynamic bond structure, which can be intercalated at the interface to achieve covalent bonding at the interface.

20. The Janus nanofiber photothermal film obtained by the preparation method according to claim 1, characterized in that, Both the PPG@PU layer and the PDMS@PU layer in the Janus nanofiber photothermal film have a DA dynamic bond structure, which enables the cracks to heal themselves when the nanofiber film breaks, by irradiating the breakage point with an infrared point light source.

21. The Janus nanofiber photothermal film obtained by the preparation method according to claim 1, characterized in that, Both the PPG@PU layer and the PDMS@PU layer in the Janus nanofiber photothermal film have a DA dynamic bond structure. After heating at 120℃ for 5-360 min, the cross-linked structure of the polymer is re-dissociated into a linear structure, which can be reprocessed by electrospinning to realize the reconstruction of the Janus nanofiber photothermal film.

22. The application of the Janus nanofiber photothermal film of claim 18 in solar-driven interfacial water evaporation.